- у - 2 7.23. 1) 1 (у - 5)(y + 2) 3 11y + 12 10 = 2- - 3 10 - y - 2) у2 + 3 у 5 3у2 + 8 у 14 2 2 1 7.24. 1) (х + 3)2 (x - 3)2 + 3x = ; 2 4 8 (3x – 4) - + 2) + (х - 1)(2х - 5) 2 1 = (x + 2)2 5 5 3) (x - 7)(x - 3) 2 2х + 8 5 6x - (5х - 3)2 2 - 1 + x + x2 x + 9 4) ) 11 - 14x + 3x2 14 + 5 2 64
№1
а) √50 > 7
√50 > √7²
√50 > √49
б) 4√6 > 3√7
√4²*6 > √3²*7
√16*6 > √9*7
√96 > √63
№2
а) √(196 * 0,64) = √(14²*(0,8)²) = 14 * 0,8 = 11,2
б) √(72*0,5)=√36=√6² = 6
в)
г) √(-2)⁶ = √((-2)³)²=(-2)³= - 8
№3
а) (√3+√2)² = (√3)²+ 2 *√3*√2 + (√2)²= 3 + 2√6 + 2 = 5 +2√6
б) (4 - √5)(4 + √5) = 4² - (√5)² = 16 - 5 = 11
в) 5√12 - 2√27 - 3√3 = 5√(4*3) - 2√(9*3) - 3√3 = 5√(2²*3) - 2√(3²*3) - 3√3 = 5*2√3 - 2*3√3 - 3√3= 10√3 - 6√3 - 3√3 = √3
№4
√(72*а⁵) = √(36*2 * а⁴*а)= √(6²*2 * (а²)² * а) = 6*а²*√(2а)
№5
№6